2009
DOI: 10.1093/ilar.50.3.282
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Effects of Intermittent Hypoxia

Abstract: Obstructive sleep apnea is characterized by repeated upper airway obstruction during sleep and affects between 5% and 20% of the population. Epidemiological studies reveal that sleep apnea and associated intermittent hypoxemia increase the risk for hypertension and vascular disease but the mechanisms underlying these effects are incompletely understood. This review reports the results of rodent models of intermittent hypoxia (IH) and relates them to the observed hemodynamic and vascular consequences of sleep a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 90 publications
0
30
0
Order By: Relevance
“…It has been suggested that the IH of OSA is more inflammatory than stable hypoxia, since cycles of hypoxia and reoxygenation bear a resemblance to ischemia-reperfusion injury which is well known to promote significant oxidative stress [31, 113, 114]. IH-induced inflammation in adipose tissues was examined in vitro by Taylor et al , who exposed primary human subcutaneous and visceral adipocytes to acute IH.…”
Section: Osa and Inflammation: Animal/cell Studiesmentioning
confidence: 99%
“…It has been suggested that the IH of OSA is more inflammatory than stable hypoxia, since cycles of hypoxia and reoxygenation bear a resemblance to ischemia-reperfusion injury which is well known to promote significant oxidative stress [31, 113, 114]. IH-induced inflammation in adipose tissues was examined in vitro by Taylor et al , who exposed primary human subcutaneous and visceral adipocytes to acute IH.…”
Section: Osa and Inflammation: Animal/cell Studiesmentioning
confidence: 99%
“…Whereas maintenance of CIH-induced hypertension is generally agreed to depend on increased systemic vascular resistance, the underlying mechanisms are complex and involve changes in vascular reactivity (1,(22)(23)(24)47) as well as chronically elevated sympathetic nerve activity (SNA) (16,32,60). The latter has been strongly linked to sensitization of the arterial chemoreflex (15,32,45,50,67), which results in tonic activation of sympathetic outflow even at normoxic arterial PO 2 .…”
mentioning
confidence: 99%
“…There is a strong association between sleep apnea and hypertension, ischemic heart disease, stroke, arrhythmia, chronic heart failure, and other cardiovascular morbidity and mortality [6,7]. Patients with sleep apnea who do not have overt cardiovascular disease can have subclinical structural and functional changes marking atherosclerosis [8] and endothelial dysfunction [9], suggesting the primary role of these processes in the development of cardiovascular morbidity.…”
Section: Cardiovascular Consequencesmentioning
confidence: 99%
“…In another study, hypocapnic (but not eucapnic) intermittent hypoxia caused more profound increases in right ventricular mass [156]. It is likely that CO 2 interferes with the development of pulmonary hypertension and modulates the pulmonary responses to hypoxia in rats exposed to chronic hypoxia [7]. Despite these differences and markedly divergent changes in arterial blood gases, the rodent model of intermittent hypoxia continues to provide good opportunities to study the mechanisms of cardiovascular comorbidity of sleep apnea.…”
Section: Intermittent Hypoxiamentioning
confidence: 99%